2015
DOI: 10.4236/health.2015.79120
|View full text |Cite
|
Sign up to set email alerts
|

Vulnerable Consumers in the Deregulated Dutch Health System

Abstract: Public service deregulation is favoured for motivating providers to offer consumers better pricequality services. Consequently, consumers are enabled to make informed choices and choose for the best service provider. However, recent publications reveal that consumers are not capable of exercising optimal choice behaviour. Despite these concerns, evidence is lacking on the extent to which potentially vulnerable consumers make use of the core element of deregulation-switching health plans. This article is meant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Research suggests that vulnerable citizens are less likely to reap the benefits of market‐based service reforms (Anttonen ; Booltink et al . ; Botti and Iyengar ; Dan and Andrews ; Jilke ). Jilke (), for example, found that socio‐economic position is a significant determinant of the quality of services citizens will receive and their ability to switch from unsatisfactory providers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Research suggests that vulnerable citizens are less likely to reap the benefits of market‐based service reforms (Anttonen ; Booltink et al . ; Botti and Iyengar ; Dan and Andrews ; Jilke ). Jilke (), for example, found that socio‐economic position is a significant determinant of the quality of services citizens will receive and their ability to switch from unsatisfactory providers.…”
Section: Discussionmentioning
confidence: 99%
“…Our data supports this ambiguity; the system for identifying and addressing emerging issues is currently informal and unfixed in the NDIS implementation; however, this will be more formalized when the proposed Quality and Safeguards Framework has been finalized. Research suggests that vulnerable citizens are less likely to reap the benefits of market-based service reforms (Anttonen 2012;Booltink et al 2015;Botti and Iyengar 2006;Dan and Andrews 2016;Jilke 2015). Jilke (2015), for example, found that socioeconomic position is a significant determinant of the quality of services citizens will receive and their ability to switch from unsatisfactory providers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation